ANALISIS EKONOMI PEMANFAATAN KAYU KELAPA DENGAN MODEL PROGRAMA DINAMIKA : Suatu Studi Kasus di Daerah Sulawesi Utara - Esry H. O H. O Laoh; B D Nasendi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
Coconut wood has been potentially available as a source of raw material for wood processing industries for many years. Coconut wood is a non-traditional forestry timber. In forestry jargon coconut wood is classified as a non-wood or non-timber product. As a source of industrial raw material for boards and planks and for fumiture components and housing utensils plenty of coconut woods are available as wood substitutes throughout Indonesia. It is technically as well as economically viable. Its investment opportunities is good and its prospects is also promising.The analysis was based on a case study which was conducted in North Sulawesi Province of eastern Indonesia using a dynamic programming aproach to identify and to analyse intertemporal investment allocation possibilities and its best altematives to gain financial and economic return. When the limited funds were to be best dicided and allocated based on scarcityresource allocation decision approach then the dynamic programming model has proven as a best choice. Eventhougk the model is not a best one but it is available to guide the decision makers to best posible alternative solutions in a decision making process.Keywords : Dynamic Progranuning Model, Coconut Wood utilization, North Sulawesi.